PENCEGAHAN DIABETES MELLITUS PADA USIA PRODUKTIF: SCREENING AWAL DAN PENYULUHAN DI DESA SRATEN KECAMATAN GATAK - Muhammad Naufal Mizan Auladi; Anggiana Mawadda Putri; Khalisha Ramdhani Santoso; Jihan Nur Azizah; Rafika Hasmi Lefia; Fairuz Salsabila Basyasyah; Fatia Hilmi Zahra; Sylfi Carmelia Dewi; Nafis Fatikhah Az-Zahra; Zahra Khoirunnisa; Ninda Khairul Nisa; Livya Apriani Rukmana; Musharrafah Musharrafah; Arif Pristianto; Kusuma Estu Werdani (Universitas Muhammadiyah Surakarta, 2026)
Diabetes mellitus is one of the chronic metabolic diseases whose incidence continues to increase, especially in productive age. This screening and counseling activity aims to detect diabetes mellitus early and provide counseling related to the prevention and management of diabetes mellitus in productive age communities in Sraten Village, Gatak District, Sukoharjo Regency. The method used includes initial screening of diabetes mellitus using blood sugar checks, blood pressure checks, and body mass index measurements. Then, participants filled out a pre-test of knowledge about diabetes mellitus, followed by counseling on diabetes mellitus, risk factors, signs and symptoms, as well as efforts to prevent and manage diabetes mellitus, and ended with filling out a post-test. A total of 50 residents of Sraten Village who are of productive age participated in this activity. The results of this activity obtained an increase in community understanding of the risk factors and symptoms of diabetes mellitus. Evaluation of this activity showed a good understanding of diabetes mellitus and enthusiasm and active participation from the community to make efforts to prevent and manage diabetes mellitus. The conclusion of this activity is the need for e arly detection and counseling related to diabetes mellitus on a regular basis to increase public awareness, especially at productive age, in efforts to prevent and manage diabetes mellitus. Suggestions that can be given are that similar activities can be carried out routinely for f ollow-up in the form of periodic monitoring and involve more participants from various age groups.